Transformasi Delapan Asnaf Zakat dalam Perspektif Maqashid Shariah Pemahaman dan Implikasi Keberlanjutan - Muhamad Syarif; Baiq Asturi Kusniawati (Universitas Muhammadiyah Mataram, 2024)
Abstract: Zakat is one of the pillars of Islam whose main goal is to reduce social inequality and ensure community welfare. In the Maqashid perspective of sharia law which refers to the main goals of Islam, zakat plays an important role in achieving social justice, general welfare, and maintaining religion. One of the concepts related to zakat is the eight asnaf of zakat, which traditionally includes eight groups of zakat recipients who are entitled accept it. This research aims to study the transformation of the eight asnaf zakat from the Maqashid Syariah perspective and determine the sustainable impact in relation to sustainable development goals (SDGs). Through an interdisciplinary approach, this research will examine the understanding of asnaf zakat in the context of social, economic and cultural development. This includes an analysis of changes in the definition and recipients of asnaf zakat in the contemporary world, as well as their impact on sustainability in a global context. It is hoped that the results of this research will provide a deeper understanding of the role of zakat in achieving the goals of Maqashid Syariah, especially in the context of the transformation of the eight asnaf of zakat. Apart from that, this research will also identify implications relevant to the SDGs, such as overcoming poverty, health, education and environmental resilience.Abstrak: Zakat merupakan salah satu rukun Islam yang tujuan utamanya adalah mengurangi kesenjangan sosial dan menjamin kesejahteraan masyrakat. Dalam perspektif Maqashid hukum syariah yang mengacu pada tujuan utama Islam, zakat memegang peranan penting dalam mencapai keadilan sosial, kesejahteraan umum, dan memelihara agama, salah satu konsep yang berkaitan dengan zakat adalah delapan asnaf zakat, yang secara tradisional mencakup delapan kelompok penerima zakat yang berhak menerimanya. Penelitian ini bertujuan untuk mempelajari transformasi delapan asnaf zakat dalam perspektif Maqashid Syariah dan mengetahui dampak berkelanjutan kaitanya dengan tujuan pembangunan berkelanjutan(SDGs). Melalui pendekatan interdisipliner, penelitian ini akan mengkaji pemahaman asnaf zakat dalam konteks pembangunan sosial, ekonomi, dan budaya. Hal ini mencakup analisis terhadap perubahan dalam definisi dan penerima asnaf zakat di dunia kontemporer, serta dampaknya terhadap keberlanjutan dalam konteks global. Hasil penelitian ini diharapkan akan memberi pemahaman yang lebih dalam tentang peran zakat dalam mencapai tujuan Maqashid Syariah, khususnya dalam konteks transformasi delapan asnaf zakat. Selain itu, penelitian ini juga akan mengidentifikasi implikasi yang relavan dengan SDGs, seperti pengatasan kemiskinan, kesehatan, pendidikan, dan ketahanan lingkungan.